Pengaruh Bauran Promosi terhadap Volume Penjualan pada Unit Produk Hilir Kopi Banaran PT. Perkebunan Nusantara IX - Dimas Ivan Fuadi; Budi Astuti (SAFE-Network, 2023)
The aim of this research is to determine the effect of the promotional mix on sales volume in the downstream product unit of Banaran coffee at PT. Perkebunan Nusantara IX. This research uses a quantitative case study method, taking secondary data, namely sales data and promotional mix for Kopi Banaran for 2021-2022 using the IBM SPSS 21 application. The results of this research show that elements have a positive and significant effect on sales volume at Downstream Kopi Banaran are advertising, sales promotion and public relations variables. Meanwhile, direct sales and personal sales variables do not have a significant effect on sales at Hilir Kopi Banaran. The variable that has the dominant influence is the promotional cost variable, which is indicated by the largest coefficient value compared to other variables.